Tirukkuṟaḷ dalam kurikulum Bahasa Tamil sekolah rendah dan menengah: Satu persepsi dan realiti ke arah pembentukan insan holistik / Annathurai Kasinadan - Annathurai, Kasinadan (2016)
Education is a process of establishing a holistic individual in one’s lifespan. In the scope of Malaysian education, holistic human being is assessed based on philosophy of education where it will create the completed and balanced mankind in the aspects of physical, emotional, spiritual and intellectual (JERI). Tirukkuṟaḷ is part and partial of Tamil literature component which is being practiced in contemporary primary and secondary school curriculum. The Tirukkuṟaḷ couplet has been applied into the curriculum as accordingly based on the four aspects mentioned above. This research is being conducted to identify the effectiveness of couplets Tirukkuṟaḷ in Tamil curriculum of primary and secondary schools toward the direction of holistic human formation. This research consists of three main scopes which is to identify the perception of Tirukkuṟaḷ, the practice of Tirukkuṟaḷ and the demographic relationship among the Tamil community in Malaysia. This research in carried out in the combination of two methods namely qualitative and quantitative. 420 people from Tamil community have been chosen randomly as a respondents from the north, middle, south and the east coast of Malaysia for the purpose of this study. 220 men and 200 ladies aged between 18 and 40 were selected as respondents for this research. Questionnaire respondents consisted of 220 men and 200 women aged between 18 and 40 years old. Apart from that,10 informant interviews were selected from various fields to strengthen the quantitative findings. The reliability of the research instrument has been evaluated at r = 0.872 and certified accordingly. The descriptive and inference method have been used for the data analysis. Descriptive method assess the perception and the practice of Tirukkuṟaḷ among Tamil community as a whole. Whereas, inference analysis using independent t-test and one-way ANOVA test were used to test the hypothesis of the study. These findings show that Malaysian Tamil community has a high perception of Tirukkuṟaḷ as a guide in life. Whereas, the influence on practicing Tirukkuṟaḷ in four elements namely physical, emotional, spiritual and intellectual is at an average level. The influence of Tirukkuṟaḷ practice on all JERI elements show medium level namely physical domain 47.85%, emotional domain 46.66%, spiritual domain 46.90%, intellectual domain 48.58% and holistic human 46.67%. While statistical analysis methods t-test independent samples showed that there were significant differences in terms of gender, women show a more holistic than men. Meanwhile in terms of the place of residence is not affected by Tirukkuṟaḷ. The results of one way ANOVA showed significant differences in terms of age and religion, while there were no significant differences in terms of education based on Tirukkuṟaḷ. These findings prove that Malaysians have a high perception of Tirukkuṟaḷ as a guide in life. However in terms of practicing them it is still in the medium level due to several factors such as age, level of education and the environment. The result also proves that life is a learning process and we should keep on learning and practicing whatever we have learnt throughout our lives. Researchers argue that relevant couplet Tirukkuṟaḷ selected and added should be implemented in Tamil curriculum of primary and secondary schools so that it can create a holistic individual as expected by the National Education Philosophy.